Use of Adolescent Problems and Risk Behaviours Inventory (IPERI) to Predict the Influence of Personal Problems on Risky Behaviour among Adolescent in Sarawak, Malaysia - Othman, Mohd. Razali; Wan Husin, Wan Nurul Izza; Mohammad Roose, Aina Razlin; Mohd Razali, Izzat Shafiq (2017)
This study explores the use of Adolescent Problems and Risk Behaviours Inventory (IPERI) to predict the relationship of personal problems on risky behaviour among adolescence aged 14 to 17. The objective of this research is to analyse the influence of personal problems such as study problem, family support, financial problem, career indecision, peer influence, spiritual management and health condition on the development of risky behaviours among adolescents. The risky behaviours consist of eight (8) behaviours which include discipline problem, physical bully, suicidal thought, free sex, tobacco consumption, alcohol abuse, drug abuse and media influence. A survey using Adolescent Problems and Risk Behaviours Inventory (IPERI) is administered to three hundred and seventy-nine (379) respondents, age between 14 to 17. The analysis of Pearson Correlation Coefficient showed the existence of significant between all the problems variables study problem (r = .316), family support (r = .256), financial problem (r = .240), health condition (r = .134), peer influence (r = .189), career indecision (r = .185) and spiritual management (r = .242), with the risky behaviour variables. This research contributes to the profiling of adolescents’ risky behaviours which can guide the development of interventions in tackling adolescent’s risky behaviour.